Upaya Meningkatkan Motivasi Dan Hasil Belajar Siswa Dengan Menggunakan Metode Kerja Kelompok Pada Mata Pelajaran Pendidikan Agama Kristen di SD Negeri 38 Ampenan - Ruth Sumarmi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
This study aims to improve student motivation and learning outcomes by using group work methods on Christianity at SD Negeri 38 Ampenan. This research method uses classroom action research methods with research subjects namely fourth grade students of SD Negeri 38 Ampenan. The research instrument used observation and tests. The research data were analyzed using descriptive qualitative and quantitative techniques. The results of this study indicate that the learning process using group work methods can increase student motivation so that it has a positive impact on the final grades obtained by students. Based on the results of observations in cycle I and cycle II, it was found that all students liked the way of learning and were motivated to learn using the group work method on the grounds that the learning process was fun and did not make it saturated.